2009
DOI: 10.1038/hr.2009.160
|View full text |Cite
|
Sign up to set email alerts
|

Olmesartan reduces oxidative stress in the brain of stroke-prone spontaneously hypertensive rats assessed by an in vivo ESR method

Abstract: We previously showed that oxidative stress in the brain is involved in the neural mechanisms of hypertension. Therefore, olmesartan, an angiotensin type 1 receptor blocker, might affect oxidative stress in the brains of stroke-prone spontaneously hypertensive rats (SHRSP). Here, we evaluated the effects of olmesartan treatment using an in vivo electron spin resonance (ESR)/spin probe technique. Two groups of SHRSP were treated with either olmesartan (10 mg kg À1 day À1 ) or hydralazine (Hyd, 20 mg kg À1 day À1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…15,[18][19][20] Peripherally administered ARBs also inhibit the central actions of angiotensin II in the brain. [21][22][23][24][25][26][27][28] Furthermore, we demonstrated that orally administered TLM inhibits SNS activation by reducing oxidative stress in the brains of hypertensive rats. 16 However, it has not been determined whether the sympathoinhibition caused by orally administered ARBs is a class effect of ARBs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,[18][19][20] Peripherally administered ARBs also inhibit the central actions of angiotensin II in the brain. [21][22][23][24][25][26][27][28] Furthermore, we demonstrated that orally administered TLM inhibits SNS activation by reducing oxidative stress in the brains of hypertensive rats. 16 However, it has not been determined whether the sympathoinhibition caused by orally administered ARBs is a class effect of ARBs.…”
Section: Discussionmentioning
confidence: 99%
“…16,[21][22][23][24][25][26][27][28] We demonstrated that orally administered ARBs reduced oxidative stress in the brains of hypertensive rats 16,27 and that orally administered telmisartan (TLM) inhibits SNS activation in hypertensive rats. 16 These results suggest that orally administered ARBs have the potential to inhibit SNS activation through reduction of oxidative stress via inhibition of AT 1 R in the RVLM.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, treatment with olmesartan was carried out in SHRSP, and brain oxidative stress was evaluated by using the in vivo electron spin resonance spectroscopy method. 83 It did not induce reflex-mediated sympathoexcitation, despite the fact that blood pressure reduction was 450 mm Hg. In contrast, treatment with hydralazine or a combination of hydralazine and hydrochlorthiazide elicited a reflex-mediated sympathoexcitation and a blood pressure reduction that was similar in extent to the reduction observed with the treatment with telmisartan or olmesartan.…”
Section: Effects Of At1 Receptor Blockers On Oxidative Stress In the mentioning
confidence: 99%
“…Importantly, the antihypertensive treatment with hydralazine or a combination of hydralazine and hydrochlorthiazide did not reduce oxidative stress in the brain including the RVLM. 12,83 PERSPECTIVES Considering the importance of the AT1 receptors in the brain, particularly in the autonomic regulatory regions, such as the RVLM, NTS and paraventricular nucleus of the hypothalamus, it should be noted that these areas contain a high density of AT1 receptors in human. 84 The AT1 receptor blockers are widely used in the treatment of hypertension.…”
Section: Effects Of At1 Receptor Blockers On Oxidative Stress In the mentioning
confidence: 99%
“…Therefore, it is plausible that chronic Ang II AT1 receptor antagonist treatment in hypertension decreases central oxidative stress and blood pressure. Interestingly, the paper from Araki et al 9 showed that chronic olmesartan treatment in stroke-prone SHR (SHRSP) rats decreased oxidative stress in the brain and norepinephrine excretion. More importantly, they showed that the same reduction in blood pressure afforded by hydralazine/hydrochlorothiazide (Hyd/HCT) did not reduce brain oxidative stress, suggesting that a specific antioxidant effect in the brain was mediated by the AT1 receptor antagonist; this effect seemed to be independent of the reduction in blood pressure.…”
mentioning
confidence: 99%